2021
DOI: 10.1186/s12879-021-06814-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 antibodies and risk factors among healthy blood donors in Luanda, Angola

Abstract: Background SARS-CoV-2 emerged in China and spread throughout the world due to its rapid transmission. The exposure rate in the healthy population is unknown, mainly in resource-limited countries. Herein, we estimated the seroprevalence of anti-SARS-CoV-2 antibodies and risk factors among blood donors in Luanda, the capital city of Angola. Methods This was a retrospective study conducted with 343 blood donors. Chi-square and logistic regression were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 25 publications
10
12
1
Order By: Relevance
“…A previous study reported that the Angolan general population is mostly from the blood group O and Rh+, 19,29,30 which is in agreement with the ndings of our study (Table 2). Despite this, our results disagree with the results of a recent study carried out in 2020 by Sacomboio et al, where they identi ed a higher prevalence of blood group B (36.4%, n = 36/99) in a population from Luanda 22 , instead of the O group.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported that the Angolan general population is mostly from the blood group O and Rh+, 19,29,30 which is in agreement with the ndings of our study (Table 2). Despite this, our results disagree with the results of a recent study carried out in 2020 by Sacomboio et al, where they identi ed a higher prevalence of blood group B (36.4%, n = 36/99) in a population from Luanda 22 , instead of the O group.…”
Section: Discussionsupporting
confidence: 93%
“…If its presence is detected without IgM, infection occurred more than one month ago; our data is similar to some studies[10] [11]. On the other hand, other authors report lower seroprevalence of 1.5% positive for IgM and 4.7% positive for IgG in Angola[12] [13]. The high prevalence obtained in our study shows a widespread community transmission of SARS-CoV-2 and a low vaccination coverage which was 0% in our donors.These results corroborate those published by Percivalle et al in Italy indicat-…”
supporting
confidence: 89%
“…30,31 However, it is worth noting that advanced age (over 40 years) has previously been described as an independent risk factor for SARS-CoV-2 infection and severity, even in Angola, as shown by our research team. 4,29,32 In addition, this study reports that adults over 40 years of age are more likely to contract viral infectious diseases and also have a high chance of developing high blood pressure with potential risk for an unfavorable cardiovascular or renal clinical outcome. In terms of ABO/Rh blood groups, it is worth mentioning at the rst stage that different from the Rh + factor that represented over 50% of the Angola population, the blood group O despite being the most prevalent, no longer represents more than 50% of the population (Table 2).…”
Section: Discussionmentioning
confidence: 84%
“…This differs from the prevalence described in a study carried out in 1973 by Spielmann and colleagues, where blood group O represented between 54 to 59% of the Angolan population, 33 suggestings a decrease of blood group O in the population over the years. Indeed, a recent study carried out by our research team, showed a signi cant increase in non-O blood groups, with special attention to blood group B, 29 which, in addition to increasing its prevalence, has been associated with the risk of arterial hypertension in the Angolan population. 34,35 There are important limitations to be considered when interpreting the results of this study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation